Islamic banks and money laundering in Malaysia: a legal compliance perspective - Mohd Yasin, Norhashimah; Nik Sulaiman, Nik Nuun Asma; Zul Kepli, Mohd Yazid (Emerald Publishing Limited, 2019)
The Anti-Money Laundering and Counter Financing of Terrorism (AML/CFT) Thematic Review of Banking & Insurance sectors conducted by Bank Negara Malaysia (BNM) in 2013 indicated that oversight functions are still inadequate in the areas of compliance, internal audit, board of directors and senior management. The oversight functions refer to the AML/CFT compliance programme, which financial institutions, including Islamic banks, are obliged to execute as a part of mitigating activities against money laundering and terrorist financing. The main purpose of this chapter is to analyse whether there is any improvement in the oversight functions at the Islamic banks in Malaysia since the release of the thematic review report by BNM on 17 September 2014. This research is important as penalty for non-compliance under Section 22 of the Anti-Money Laundering, Anti-Terrorism Financing and Proceeds of Unlawful Activities Act 2001 (AMLATFPUAA) is severe. Section 22 of AMLATFPUAA entails personal responsibility on the compliance officer of an Islamic bank and not the reporting institution as a whole. Qualitative research method via interview is employed to gauge the extent of Islamic banks’ adherence to AML/CFT compliance programme. This chapter is significant as it provides Islamic banks and future researchers with the details of the compliance study as well as the current status of AML/CFT compliance programme within the Islamic banks in Malaysia.